2006
DOI: 10.1038/sj.bjc.6602952
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial cells and angiogenic serum factors during neoadjuvant chemotherapy of primary breast cancer

Abstract: Circulating endothelial cells (CECs) as well as bone-marrow-derived endothelial precursor cells (EPC) play an important role in neovascularisation and tumour growth. To study the impact of neoadjuvant chemotherapy on the amounts of CEC and their precursor cells, mature CEC and their progenitors were quantified by flow cytometry in peripheral blood of breast cancer patients during anthracycline and/or taxane based neoadjuvant chemotherapy and subsequent surgery in comparison to age-matched healthy controls. Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
167
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 28 publications
13
167
1
4
Order By: Relevance
“…Several other investigators have shown that exogenous G-CSF administration increases the levels of circulating EPCs, ECs, and angiogenesis in adult, tumor-free human subjects and mice [7,33,62], as well as the growth of fibrosarcoma, colon and lung cancers in animal models [63][64][65][66]. Similar to our results, Beerepoot et al [43] and Fürstenberger and coinvestigators [67] have also shown that the levels of circulating endothelial cells (CECs) are higher in breast cancer patients when compared to healthy subjects. Additionally, Beerpoot et al found that the levels of CECs in breast and other cancer patients with progressive disease correlated with levels of therapeutic G-CSF and chemotherapy, but not with the plasma levels of VEGF, SCF, or other cytokines and growth factors frequently reported to mobilize EPCs [4,7,41].…”
Section: Cd34supporting
confidence: 82%
“…Several other investigators have shown that exogenous G-CSF administration increases the levels of circulating EPCs, ECs, and angiogenesis in adult, tumor-free human subjects and mice [7,33,62], as well as the growth of fibrosarcoma, colon and lung cancers in animal models [63][64][65][66]. Similar to our results, Beerepoot et al [43] and Fürstenberger and coinvestigators [67] have also shown that the levels of circulating endothelial cells (CECs) are higher in breast cancer patients when compared to healthy subjects. Additionally, Beerpoot et al found that the levels of CECs in breast and other cancer patients with progressive disease correlated with levels of therapeutic G-CSF and chemotherapy, but not with the plasma levels of VEGF, SCF, or other cytokines and growth factors frequently reported to mobilize EPCs [4,7,41].…”
Section: Cd34supporting
confidence: 82%
“…For example, elevated levels of soluble CD105 have been found in the plasma of breast cancer patients when compared with normal controls, and particularly high levels have been linked with metastatic disease (Li et al, 2000a, b). Furstenberger et al (2006) recently looked at changes in serum levels of soluble angiogenesis-related factors in breast cancer patients receiving anthracycline or taxane-based neoadjuvant chemotherapy. Although there were no differences in baseline levels of soluble CD105 between patients and controls, they found that patients demonstrated significant decrease in circulating levels of soluble CD105 after two cycles of chemotherapy (Po0.01).…”
Section: Discussionmentioning
confidence: 99%
“…68 Consistent with their role in tissue regeneration, EPCs are also recruited when the tumor vasculature is destroyed by chemo/radiation therapy, both in preclinical models as well as in clinical studies. [69][70][71] 74 and why EPC levels rebound in glioblastoma patients during drugfree intervals of a pan-VEGF inhibitor. 25 In breast cancer patients during drug-free intervals after chemotherapy, EPCs increase similarly, concomitant with a rise of plasma VEGF and other pro-angiogenic cytokines.…”
Section: Role Of Endothelial (Progenitor) Cells In Anti-angiogenic Esmentioning
confidence: 99%